Unusual Isolated Parapharyngeal Second Branchial Cleft Cyst: A Case Report and Literature Review - Emad A. Magdy; Geylan A. Fadali; Mahmoud Seif-Elnasr; Mohamed F. Fathalla (Case Reports in Otolaryngology)
Second branchial cleft cysts (BCCs) are common congenital causes of neck swellings; however, isolated parapharyngeal space presentation is extremely rare, with only sporadic cases reported. Our objectives in this report are to describe a case and review different diagnostic and management strategies adopted in the current world literature. The case presented is a 26-year-old female with a large isolated parapharyngeal BCC extending to skull base in which first presenting symptoms were referred otalgia and painful side-to-side head rotation for months followed by odynophagia. A previously ordered computed tomography (CT) scan suspected a parapharyngeal abscess. Correct diagnosis was preoperatively achieved using magnetic resonance imaging (MRI) showing a 3.1 × 3.4 × 5.4 cm parapharyngeal BCC. Cyst was completely surgically excised transoral without complications. No evidence of recurrence has been noted after 24-month follow-up. A comprehensive world literature search for all reported cases in the last 30-years revealed thirty cases in 23 separate case reports with different diagnostic and surgical modalities adopted. Presentation and management strategies in such rare cases are discussed in detail. Our study shows that although rare, BCC diagnosis should be kept in mind while dealing with isolated parapharyngeal space swellings with MRI being key for successful preoperative diagnosis. If encountered, the transoral route can be a safe, aesthetically pleasing and effective way for complete surgical excision in contrast to most other parapharyngeal swellings, which are usually better excised via a transcervical approach.